STANDAR MUTU PENDIDIK DAN TENAGA KEPENDIDIKAN MADRASAH/PESANTREN/PT/PTKIN: IMPLEMENTASI DAN PROBLEMATIKA - Nordianingsih, Meltani; Dakir, Dakir (STKIP Pesisir Selatan, 2025)
This article aims to analyze the quality standards for educators (teachers, lecturers, ustadz/ustadzah) and educational staff (administrative staff, lab assistants) in Islamic educational institutions, such as madrasah, pesantren, Higher Education Institutions (HEIs), and State Islamic Religious Colleges (PTKIN). Using a qualitative approach with literature studies and policy analysis, this research examines the implementation of quality standards regulated by national (Ministry of Education and Ministry of Religious Affairs regulations) and local policies, as well as the problematics encountered in the field. The findings reveal that although quality standards—covering academic qualifications, pedagogical and professional competencies, and integration of Islamic values—have been clearly formulated, their implementation still faces challenges, including regional disparities in educator quality, limited funding, resistance to modern management systems, and overlapping regulations. Case studies in madrasah, pesantren, and PTKIN highlight that quality improvement requires synergies between continuous training, technology adoption, and adaptation to local wisdom. This article recommends the need for more inclusive policies, sustainable funding, and strengthened inter-institutional collaboration to optimize quality standards in the globalization era.